Projeto e implementação de um pré-regulador de fator de potência aplicado a lâmpadas fluorescentes t5 com fluxo luminoso variável - Reginatto, Paulo Ricardo Alves (2016)
In this master thesis, the development of an electronic ballast with variable luminous flux for a T5 fluorescent lamp is presented. Several technics for the control of the power variation have already been discussed in the literature. Therefore, this work presents a method that blends two of the most traditional technics: the control done by altering the bus voltage and the control done through the changing of the switching frequency. To achieve this, the electronic circuit is composed by a power factor pre-regulator, which is a SEPIC converter with digitally controlled output voltage, a half-bridge inverter and a LCC resonant filter. For the pre-regulation stage, a proportional-integral compensator is used as the control method, which provides different levels of output voltage with an almost zero error when compared to the reference voltage and a satisfactory response to line disturbances. The half-bridge inverter control is done with the IR21592 IC, which keeps the phase angle fixed for the system’s entire operation band through a phase control loop. In order to validate the efficiency of this method, the electronic circuit is also evaluated when operating with the classical approach, by using a constant bus voltage and controlling the phase angle of the resonant filter to change the lamp’s luminous flux. Furthermore, the pre-heating of the lamp ’s filaments is analyzed and its temperatures are controlled by a Flyback converter, according to the power variation.